ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONDISI FINANCIAL DISTRESS BANK PERKREDITAN RAKYAT - Effendi, Satrio Arga; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2016)
This research aimed to analyze the factors affecting the financial distress of rural banks in West Sumatera. By using the technique of multiple linear regression analysis, and  the  latest  prediction  model  of  financial  distress  "Hebb  Z-Score",  this  research focuses on analyzing the influence of Current Ratio (CR), Total Liabilities to Total Assets (TLTA), Net Profit Margin (NPM), Non Performing Loan (NPL), and Capital Adequacy Ratio (CAR) on the financial distress of Rural Banks in West Sumatera during the period 2013-2015.The sampling method used in this research is purposive sampling with criteria of banks listed on the Financial Services Authority, and has published the annual report for the period 2013-2015. This research obtained 87 rural banks as samples. Source of research data obtained from published financial statements of each bank listed in the directory Financial Services Authority (FSA).The results of this study indicate that TLTA and NPL ratio had a negative effect on the Z-Score, which it means that the NPL and TLTA   had a positive effect on the probability of financial distress banks. The higher the liabilities owned by bank and number of bad debts, the higher risk of a bank run into financial distress. NPM ratio has a positive influence on the value of the Z-Score, which it means that the NPM negatively affect probabilitias financial distress. The higher the value of NPM, the banks are increasingly safe and avoid the risk of distress. In addition it was found that the ratio of CR and CAR have no effect on financial distress.